2011
DOI: 10.1099/ijs.0.022525-0
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium actinocoloniiforme sp. nov. and Bifidobacterium bohemicum sp. nov., from the bumblebee digestive tract

Abstract: Our previous study, based primarily on PCR-denaturing gradient gel electrophoresis and 16S rRNA gene sequencing, focused on the isolation of four bifidobacterial groups from the digestive tract of three bumblebee species. In that study, we proposed that these isolated groups potentially represented novel species of the family Bifidobacteriaceae. One of the four, Bifidobacterium bombi, has been described recently. Strains representing two of the other groups have been classified as members of the genus Bifidoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 30 publications
(44 reference statements)
0
31
0
Order By: Relevance
“…2a). We showed that the Enterobacteriaceae bacteria are not exotic and most of the OTUs correspond with Genbank entries linked with hosts as Apis , Bombus , and other insects (Table I) (Anderson et al 2013;Killer et al 2011). We believe this is an important observation because Enterobacteriaceae are not regarded as core gut microbiota in social bees.…”
Section: Sobsmentioning
confidence: 95%
See 1 more Smart Citation
“…2a). We showed that the Enterobacteriaceae bacteria are not exotic and most of the OTUs correspond with Genbank entries linked with hosts as Apis , Bombus , and other insects (Table I) (Anderson et al 2013;Killer et al 2011). We believe this is an important observation because Enterobacteriaceae are not regarded as core gut microbiota in social bees.…”
Section: Sobsmentioning
confidence: 95%
“…Looking to alpha diversity (Fig. 2b), we detected no differences in community richness (Sobs: P =0.306 and Chao1: P =0.507), but a significant difference in community diversity (Shannon: Killer et al (2011) Names in bold refer to OTU abbreviations used in this paper in agreement with classification in literature Plasticity in reared B. terrestris nests moved to outdoors P =0.002) in the group of young workers born in the old nest (O n Y b ). Indeed, the evenness of the gut microbiota is different in these young bumblebees due to the major uptake of new OTUs, especially Gamma-E2.…”
Section: Newborn Workers Showed a Gut Microbiota Shift With A Major Cmentioning
confidence: 95%
“…The phylum Actinobacteria also comprises, among others, Actinomycetaceae, propionibacteria, corynebacteria, mycobacteria and streptomyces [103,149]. Thirty-nine species have been assigned to the genus Bifidobacterium, including recent additions such as Bifidobacterium tsurumiense [91] isolated from hamster dental plaque, Bifidobacterium mongoliense isolated from airag, a traditional Mongolian fermented horse milk product [160], Bifidobacterium crudilactis extracted from French raw milk and raw milk cheeses [20], Bifidobacterium psychraerophilum, originating from pig intestine [128], and three bifidobacterial species, Bifidobacterium bombi [52], Bifidobacterium actinicoloniformis and Bifidobacterium bohemicus [51], isolated from the digestive tract of different bumblebee species (Table 1). Furthermore, it seems that many bifidobacteria are still to be discovered as suggested by various metagenomic studies [11,137].…”
Section: Bifidobacteriamentioning
confidence: 99%
“…animalis Chicken, rat, rabbit and calf faeces; river; ex [120] subsp. lactis Fermented milk ex [77] B. asteroides Hindgut of honeybee [122] B. bifidum Adult intestine, human faeces, vagina [93] B. bohemicus Bumblebee intestine [51] B. bombi Bumblebee intestine [52] B. boum Bovine rumen; piglet faeces [121] B. breve Infant intestine, faeces, vagina [106] B. catenulatum Child and adult intestine, vagina [119] B. choerinum Pig faeces [121] B. coryneforme Hindgut of honeybee [9] B. crudilactis Raw milk and raw milk cheese [20] B. cuniculi Rabbit faeces [121] B. dentium Human dental caries, faeces, human vagina [119] B. gallicum Adult intestine (Lauer, 1990)…”
Section: Bifidobacterial Genomesmentioning
confidence: 99%
“…The ecological distribution of bifidobacteria spans a wide range of hosts including not only mammals but also birds and social insects (4). Currently, the genus Bifidobacterium encompasses 48 taxa, representing 39 species and 9 subspecies (2,(5)(6)(7)(8). The DNA-DNA reassociation method has been considered the cornerstone of (bifido)bacterial taxonomy (5).…”
mentioning
confidence: 99%